2011
DOI: 10.1038/ncb2281
|View full text |Cite
|
Sign up to set email alerts
|

A SNX3-dependent retromer pathway mediates retrograde transport of the Wnt sorting receptor Wntless and is required for Wnt secretion

Abstract: Wnt proteins are lipid modified glycoproteins that play a central role in development, adult tissue homeostasis and disease. Secretion of Wnt proteins is mediated by the Wnt-binding protein Wntless (Wls), which transports Wnt from the Golgi network to the cell surface for release. It has recently been shown that recycling of Wls through a retromer-dependent endosome-to-Golgi trafficking pathway is required for efficient Wnt secretion, but the mechanism of this retrograde transport pathway is poorly understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
377
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(395 citation statements)
references
References 56 publications
17
377
1
Order By: Relevance
“…Another line of evidence endorsing that Retromer activity is associated with AD pathogenesis came from the clinical epide-miological studies. It has been reported that the mutations of SNX3 [61,66], which has been shown as an essential component of Retromer in sorting wntless, is genetically associated with AD [67]. These data supported an association between Retromer deficiency and neurodegeneration, and suggested parallel increases in A generation.…”
Section: Retromer and App Processingsupporting
confidence: 75%
“…Another line of evidence endorsing that Retromer activity is associated with AD pathogenesis came from the clinical epide-miological studies. It has been reported that the mutations of SNX3 [61,66], which has been shown as an essential component of Retromer in sorting wntless, is genetically associated with AD [67]. These data supported an association between Retromer deficiency and neurodegeneration, and suggested parallel increases in A generation.…”
Section: Retromer and App Processingsupporting
confidence: 75%
“…However, a formal test of this hypothesis is lacking. Retromer binds sorting nexin 3 [henceforth referred to as SNX3 (human) or Snx3 (yeast)] (12)(13)(14)(15), and in SNX3 knockdown cells, less retromer is associated with endosomes (14). In this study, we show that SNX3 and RAB7 are coordinately recognized by retromer and that these interactions are sufficient to recruit retromer to a membrane where they poise retromer to capture integral membrane retrograde cargo.…”
mentioning
confidence: 68%
“…1A) (16) that we speculate serves as an interaction surface for binding other factors such as retromer and/or cargo proteins. Because both human and yeast SNX3 associate with retromer (12,13,17), we implemented a functional assay in yeast to determine whether residues on this surface are required for the function of yeast Snx3 in vivo, and then extended this information to human SNX3. Two or three codons encoding residues (depending on the length of the strand) with solvent-exposed side chains were changed to alanine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although a recent study failed to show a VPS35 RNAi effect in Madin-Darby canine kidney cells on TGFβR1(ALK5) (34), they did demonstrate that TGFβRII was mislocalized to both the basolateral and apical membrane, as opposed to its normal localization to the basolateral membrane. Examination of the role of the retromer complex on BMP signaling in Drosophila has been incongruent (27,35,36). On the basis of our genetic and cell biological data, as well as the preliminary data from the mammalian proteomic analysis, it is very likely that retromer-dependent regulation of type I BMP and Activin receptors is a conserved mechanism of TGFβ-receptor regulation.…”
Section: Discussionmentioning
confidence: 99%
“…To test directly whether type I receptor SMA-6 recycling is dependent on the retromer pathway, we analyzed receptor localization in mutants lacking the core retromer subunit VPS-35 (vacuolar protein sorting factor-35) and several sorting nexins (SNX-1, SNX-3, and SNX-27) that may be specific for particular subsets of retromer-dependent cargo (24)(25)(26)(27). Expression of the RAD-SMAD GFP reporter in wildtype, sma-6(wk7), and arf-6(tm1447) staged at L3 (n = 6).…”
Section: Clathrin-dependent Endocytosis Is Necessary For Bmp Receptormentioning
confidence: 99%